Assessment of abdominal obesity prevalence and determinants among adults in southwest Ethiopia: a cross-sectional study - Yosef, Tewodros; Sebeta, Asresash; Tekalign, Eyob; Sisay, Binyam Girma; Bekele, Bayu Begashaw; Tesfaw, Aragaw; Shifera, Nigusie (Frontiers in Public Health, 2024)
Background Abdominal obesity, excess fat around the abdomen, is more harmful than other fat types and is a key diagnostic criterion for metabolic syndrome. It poses a growing global public health concern. This study aimed to assess the prevalence of and determinants of abdominal obesity among adults in southwest Ethiopia. Methods A cross-sectional study involving 624 adults in Semen Bench district, southwest Ethiopia was conducted from May 23 to June 23, 2022. The data was gathered using questionnaires and anthropometric measurements. The data were analyzed using Stata version 18. A robust Poisson regression was used due to the abdominal obesity prevalence exceeding 10%. Variables with p-values < 0.25 in the bivariate analysis were included in the multivariable analysis. The adjusted prevalence ratio (APR) and 95% confidence interval were reported to indicate statistical significance and the strength of associations. Results The prevalence of abdominal obesity was 18% (95% CI: 15–21%). After adjusting for confounding variables, the determinants of abdominal obesity included participants aged 31–50 (APR = 3.62, 95% CI: 2.67–8.95) and 51–65 (APR = 3.24, 95% CI: 2.51–8.69), being female (APR = 2.65, 95% CI: 1.63–4.98), having a low wealth index (APR = 1.46, 95% CI: 1.19–3.76), physical inactivity (APR = 1.39, 95% CI: 1.06–4.18), lack of adequate dietary diversity (APR = 3.08, 95% CI: 2.09–6.42), and food insecurity (APR = 2.84, 95% CI: 1.82–7.68). Conclusion The research revealed that 18% of the participants exhibited abdominal obesity. Factors such as advanced age, being female, having a low wealth index, physical inactivity, insufficient dietary diversity, and food insecurity were identified as contributors to abdominal obesity. Therefore, it is crucial to develop targeted interventions to address modifiable factors, as this can also help prevent the onset of non-communicable chronic diseases associated with abdominal obesity.